Optimization of hyperglycemic induction in zebrafish and evaluation of its blood glucose level and metabolite fingerprint treated with psychotria malayana Jack Leaf extract - Benchoula, Khaled; Khatib, Alfi; Quzwain, Fairuz M. C.; Che Mohamad, Che Anuar; Wan Sulaiman, Wan Mohd Azizi; Abdul Wahab, Ridhwan; Ahmed, Qamar Uddin; Abdul Ghaffar, Majid; Saiman, Mohd Zuwairi; Alajmi, Mohamed Fahad; El-Seedi, Hesham (MDPI, 2019)
A standard protocol to develop type 1 diabetes in zebrafish is still uncertain due to unpredictable factors. In this study, an optimized protocol was developed and used to evaluate the anti-diabetic activity of Psychotria malayana leaf. The aims of this study were to develop a type 1 diabetic adult zebrafish model and to evaluate the anti-diabetic activity of the plant extract on the developed model. The ability of streptozotocin and alloxan at a different dose to elevate the blood glucose levels in zebrafish was evaluated. While the anti-diabetic activity of P. malayana aqueous extract was evaluated through analysis of blood glucose and LC-MS analysis fingerprinting. The results indicated that a single intraperitoneal injection of 300 mg/kg alloxan was the optimal dose to elevate the fasting blood glucose in zebrafish. Furthermore, the plant extract at 1, 2, and 3 g/kg significantly reduced blood glucose levels in the diabetic zebrafish. In addition, LC-MS-based fingerprinting indicated that 3 g/kg plant extract more effective than other doses. Phytosterols, sugar alcohols, sugar acid, free fatty acids, cyclitols, phenolics, and alkaloid were detected in the extract using GC-MS. In conclusion, P. malayana leaf aqueous extract showed anti-diabetic activity on the developed type 1 diabetic zebrafish model.